Tendon and ligament injury-associated gene variants and history of soft tissue injury in elite rugby athletes - Brazier, J.; Antrobus, M. R.; Raleigh, S. M.; Cullen, T.; Stebbings, G. K.; Day, S. H.; Herbert, A.; Heffernan, S. M.; Callus, P.; Kilduff, L. P.; Erskine, R. M.; Williams, A. G. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: There is a genetic component to tendon and ligament injuries which is highly likely to be polygenic in nature. Elite rugby has one of the highest reported injury incidences of any professional sport with some of the most severe injuries affecting tendons and ligaments. Thus, this study investigated if suspected tendon and ligament injury-associated polygenic profiles of elite rugby athletes (RA) with a history of prior tendon and ligament injury differed from RA with no history of injury. We hypothesised that tendon and ligament injury-associated genotypes and polygenic profiles would be overrepresented in RA with a history of soft tissue injury compared to RA with no history of injury. METHODS: Participants from the RugbyGene project were elite white male RA (n = 133; mean (standard deviation) height 1.86 (0.07) m, mass 102 (12) kg, age 26 (5) yr), including 111 rugby union athletes and 22 rugby league athletes. Soft-tissue injury history was collected utilising a self-reported questionnaire. PCR of genomic DNA was used to determine genotypes using TaqMan probes, then groups were compared using *2 and odds ratio (OR) statistics, with alpha set at P< 0.02). Furthermore, C-allele carriers were overrepresented, whilst the TT genotype was underrepresented in NIL (86.9% and 17.1%) compared to ligament sprain (LS) (69.8% and 30.2%, P < 0.02). NIL had 3.5 times the odds of carrying the CC genotype compared to LR. For MMP3 rs679620, the T allele was overrepresented and C-allele carriers underrepresented in non-injured tendon group (NIT) (23.5%, 44.7% and 76.5%, respectively) compared to the tendinopathy group (TY) (5.7%, 28.6 and 94.3%, P < 0.03). Additionally, the C-C inferred haplotype frequency of COL5A1 rs12722 and COL5A1 rs3196378, respectively, was higher in NIL and the all non-injured athlete group compared to LR, LS and the all-injured athlete group (P < 0.01). Furthermore, the C-A-G inferred haplotype frequency of MMP3 rs591058, rs650108 and rs679620 was lower in NIT than tendon rupture group (P < 0.01). CONCLUSION: The current data suggest that elite rugby athletes with no history of soft-tissue injury appear to have inherited more resistance to soft tissue injury than their injured peers. The current study provides further insight into the detailed aetiology of musculoskeletal soft tissue injuries within elite rugby and may, in future, be worthy of consideration for managing the interindividual variability of injury risk in rugby.